Numerical study of high-temperature cascaded packed bed thermal energy storage system. (September 2022) - Sun, Y.S.; Han, Y.; Li, G.D.; Shen, H.Y.; Chi, X.M.; Zhang, C.Y.
Abstract: The thermal energy storage system (TES) in the form of packed bed with encapsulated phase change materials (EPCMs) can further improve the thermal performance of ordinary TES. This study presents a numerical model for a three-dimensional cascaded packed bed thermal energy storage system (PBTES), in which an effective thermal conductivity model is used by consisering the natural convection effects in each EPCM based on its volume average liquid fraction. To examine the system-storage thermal energy and exergy in PBTES accurately, a thermodynamic analysis approach is also given. The high-temperature PCMs are grouped as KNO3, NaNO3, and NaNO2 according to the phase transition temperature from high to low in the packed bed stage. The effects of element stages on the thermal performance of PBTES are studied. Results show that the total thermal energy storage of cascaded-PBTES is 38.5% higher than that of single-PBTES (KNO3 ), and the total thermal exergy storage is 30.8% higher than single-PBTES. The average exergy efficiency possessed by cascaded-PBTES is 5% higher than that of single-PBTES. Furthermore, the effects of heat transfer fluid (HTF) inlet temperature and mass flow rate on the thermal performance of cascaded-PBTES are discussed. The increase of inlet temperature and mass flow rate can promote the charging process and influence the exergy efficiency. However, increasing the inlet mass flow rate will not lead to an increase in maximum thermal energy and exergy storage capacity.